Highly Isotactic Poly(N-butenyl-carbazole): Synthesis, Characterization, and Optical Properties - Antonio Botta; Vincenzo Venditto; Alfredo Rubino; Stefania Pragliola (Journal of Chemistry)
The synthesis of isotactic poly(N-butenyl-carbazole) (i-PBK) by using homogeneous isospecific Ziegler-Natta catalytic system is reported. The achieved polymer is crystalline and shows, to DSC and X-ray analysis, two distinct crystalline phases. i-PBK FTIR spectrum and X-ray diffraction pattern are compared with those of poly(N-vinylcarbazole) (PVK). The observed differences are tentatively associated with higher flexibility of the i-PBK chains due to the alkylene group connecting the carbazole group to the main chain. i-PBK optical properties are also compared with those of PVK and isotactic poly(N-pentenyl-carbazole) (i-PPK), a higher homologue of i-PBK recently used as emitting layer in organic light emitting diodes (OLEDs) showing white light emission. The close similarity of the fluorescence spectra of i-PBK and i-PPK is a promising basis for optical applications of this polymer.